THE ANALYSIS OF SPOT REPAIR JOB IN AUTOMOTIVE BODY REPAIR INDUSTRIES - Afri Yudantoko (Universitas Sultan Ageng Tirtayasa, 2019)
The aim of this study are to formulate several facts in the automotive body repair industries regarding: (1) the competency profile of spot repair job and (2) the equipment and materials needed in each spot repair job profile. This research is a descriptive quantitative study with survey research methods. Data collection techniques in this study used a closed-open combination questionnaire. This study involved 56 respondents (mechanics, foremen, and service advisors) from the automotive body repair industries at Honda, Toyota and Nissan official workshops. The results showed that; (1) there are 16 points of competency profile of spot repair job needed in order to complete the work and supplemented by 3 additional points of competence suggested and, (2) there are 45 items of equipment and 19 items of materials that are overall needed in completing all stages of spot repair job on automotive body repairs.